Retroperitoneal teratoma with obstructed hemivagina and ipsilateral renal agenesis (OHVIRA) syndrome in infant - Tamaki Iwade (Elsevier, 2021)
The reports of retroperitoneal teratoma or obstructed hemivagina and ipsilateral renal agenesis (OHVIRA) syndrome were published respectively. But there were no reports of retroperitoneal teratoma with OHVIRA syndrome. Thus, we report a rare case of retroperitoneal teratoma with OHVIRA syndrome.